THE EFFECT OF REGULATION, TRANSPARENCY, ACCOUNTABILITY, AND MONITORING EVALUATION ON THE OPTIMIZATION OF LOCAL GOVERNMENT ASSETS OF THE MEUSERAYA CENTER OF ACEH PROVINCE - Syauki Ramadhan, M; Fitri, Isnen; Talarosha, Basaria (Penerbit Lafadz Jaya, 2026)
This study aims to analyze the effect of regulation, transparency and accountability, as well as evaluation and monitoring on the optimization of regional government assets, with a case study of the Balai Meuseraya building in Aceh Province. The research is motivated by the low utilization of regional assets, which has resulted in idle assets that do not contribute optimally to Local Own-Source Revenue (PAD). A quantitative approach was employed using a survey method involving 97 civil servants of the Aceh Provincial Government engaged in asset management. The data were analyzed using multiple linear regression. The results indicate that regulation has a significant effect on asset optimization, transparency and accountability also shows a significant influence, while evaluation and monitoring have the strongest effect. Simultaneous testing confirms that all three variables jointly have a significant impact on the optimization of the Balai Meuseraya asset. These findings highlight that effective asset optimization depends on consistent regulatory implementation, transparent accountability systems, and continuous evaluation and monitoring mechanisms. This study recommends strengthening technical regulations, implementing digital asset management systems, and enhancing public participation in oversight to ensure strategic and sustainable utilization of regional government assets.